Decrypting soil microbial communities using metagenomic approaches - Delmont, Tom (CCSD, 2011)
Microbial ecology is beginning to interact with metagenomics and many microbiologists are attracted to metagenomics in the hope of discovering novel relationships between microorganisms and/or confirming that work done on isolates applies to the remaining uncultured members of the different ecosystems. With a growing number of available metagenomic datasets, metagenomes can be intensively mined by microbial ecologists in search of previously undetected correlations (both structural and functional). Here, we provide a preliminary exploration of 77 publically available metagenomes corresponding to DNA samples extracted from oceans, atoll corals, deep oceans, Antarctic aquatic environments, Arctic snows, terrestrial environments (sediments, soils, sludges, microbial fuel cell anode biofilms, acid mine drainage biofilms), polluted air, and animal and human microbiomes (human feces, mouse and chicken cecum, and cow rumen). Results show well-defined environmental specificities that emphasize microbial adaptation and evolution capabilities. Unexpected observations were also made for several ecosystems, thus providing new hypotheses about the life style of their microbial communities. Available metagenomes are a gold mine of underexploited information that could be used to explore specific microbial structural and functional relationships. The statistical analysis provided here depends in part on replicates from the different ecosystems. With the continued emphasis on metagenomic sequencing, future analyses should support rigorous statistical treatment. This preliminary metagenomic decryption could represent a pilot-scale test for a future Earth microbiome global comparison Les données présentées dans ce manuscrit de thèse sont principalement basées sur l'analyse de séquences d'ADN extraites directement de l'environnement (et en particulier du sol) en les comparant aux données cumulées au fil des siècles sur les microorganismes cultivés en laboratoire. Les objectifs, difficultés, résultats et perspectives de cette ...